"Putting the cult in cultivate": a rhetoric of guerrilla gardening in Green Valentine. Issue 2 (2nd April 2020) - Pâquet, Lili
ABSTRACT: Green Valentine: (2015), by Australian author Lili Wilkinson, is a young adult romance in which two teenagers rebel against their local council by guerrilla gardening. By taking part in an illegal activity, the protagonists of Green Valentine stage a political protest that stands in for their voices, which are silenced in public debates about the environmental future that they will inherit. Throughout this article, I examine the rhetoric of guerrilla gardening represented in Green Valentine . While the protagonists are too young to vote, their gardening is an active argument that communicates their political hopes. I conclude that the rhetoric of gardening in Green Valentine underscores the importance of community and political action to stop the capitalist production of spaces that impair the environmental future.